Diamond coating thread core head and preparation method and application thereof
By using the CVD method to form a diamond coating on the surface of the cemented carbide threaded core head, the problems of severe wear and difficulty in ensuring the accuracy of the threaded core head in the prior art are solved, and the effect of significantly improving service life and processing efficiency is achieved.
Patent Information
- Application Number
- CN202411647509.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-04
AI Technical Summary
The cemented carbide threaded core heads of existing internal thread copper pipe drawing molds have problems such as severe wear, difficulty in ensuring accuracy, and large consumption of threaded core heads, which are difficult to effectively extend the service life.
A diamond coating is formed on the surface of the cemented carbide threaded core head by chemical vapor deposition (CVD), including diamond micropowder layer, diamond coarse crystal base layer and diamond ultrafine crystal surface layer. This coating is used to significantly improve the wear resistance and bonding force of the threaded core head.
It effectively improves the service life of the threaded core head, improves the processing output of the internal threaded copper pipe, reduces costs, and improves the working efficiency of the threaded core head as a drawing mold.
Smart Images

Figure CN119554486A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of internal thread copper tube drawing dies, and in particular to a diamond-coated thread core head and a preparation method and application thereof. Background Art
[0002] Copper tubes are used in both air conditioner condensers and evaporators. As air conditioners have higher and higher requirements for energy efficiency, volume and environmental protection, internally threaded copper tubes have a large internal surface area per unit length that is 2 to 4 times that of plain tubes, and their heat exchange efficiency is greatly improved compared to plain tubes. They are gradually replacing plain tubes and becoming the mainstream copper tube type for condensers and evaporators.
[0003] Drawing internal thread copper tube is the main production method of internal thread copper tube. The inner wall thread of copper tube is obtained by processing the thread core die. The thread core die has a certain number and shape of groove teeth, which is used to form the internal thread or groove. However, its wear resistance is limited, the service life is short and the production cost is high. Certain technical means are needed to extend the service life of carbide thread core to achieve the purpose of reducing costs and increasing efficiency of enterprises.
[0004] To this end, Chinese invention patent application CN 112877618 A discloses a method for improving the service life of an internal thread core head, which includes the following production steps: S1, processing the internal thread core head; S2, placing the internal thread core head in a tray; S3, placing the tray in a vacuum temperature control box; S4, introducing liquid nitrogen to make the temperature reach -150℃~-200℃; keeping warm for 1~3 hours; S5, stopping the liquid nitrogen filling after keeping warm; raising the temperature in the box to 150℃~200℃, keeping warm for 1~3 hours; S6, taking the tray out of the vacuum temperature control box and placing it in a vacuum drying oven, naturally cooling it to room temperature and taking it out as a finished product. The method provided in the above patent application can reduce the internal micro stress of the internal thread core head, and at the same time weaken the grain boundary embrittlement effect, exert the grain boundary strengthening effect, improve the performance of the internal thread core head, and improve the service life of the internal thread core head.
[0005] However, the above patent application is difficult to break through the inherent limitations of cemented carbide such as hardness and wear resistance. The threaded core heads produced still have problems such as severe wear, difficulty in ensuring accuracy, and high consumption of threaded core heads. Summary of the invention
[0006] The hardness of diamond is as high as HV10000, which is about five times that of cemented carbide (HV1800-2200). It also has excellent properties such as high wear resistance, good thermal conductivity, low friction coefficient, and high chemical stability. However, diamond is difficult to be directly processed into complex shapes. CVD coated diamond technology can deposit diamonds on complex-shaped cemented carbide substrates, effectively improving the life of cemented carbide tools and molds. Diamond coating is a coating with extremely high wear resistance, good anti-adhesion, and strong thermal conductivity. The thickness of the diamond coating by the CVD method can reach more than 10 microns, and it has the characteristics of high strength, good toughness, and good wear resistance. Based on this, the present invention combines chemical vapor deposition (CVD) to form a diamond coating on the surface of a cemented carbide threaded core head, which can effectively improve the service life of the threaded core head, thereby facilitating the improvement of the processing output of internally threaded copper tubes and reducing costs. Therefore, the present invention provides a diamond-coated threaded core head and its preparation method and application.
[0007] Specifically, a diamond-coated threaded core head comprises a cemented carbide substrate and a diamond coating formed on the surface of the cemented carbide substrate, wherein the diamond coating comprises a diamond micropowder layer, a diamond coarse-crystalline bottom layer and a diamond ultrafine-crystalline surface layer formed on the surface of the cemented carbide substrate, and the diamond coarse-crystalline bottom layer is stacked between the diamond micropowder layer and the diamond ultrafine-crystalline surface layer, wherein the surface roughness of the diamond ultrafine-crystalline surface layer is less than 100 nm.
[0008] The diamond powder layer is mainly formed by the seeds formed by treating the cemented carbide substrate with the diamond powder suspension. The seed particles have a small particle size and can be fully filled into the surface of the cemented carbide substrate, effectively increasing the contact area between the diamond coating and the surface of the cemented carbide substrate, increasing the bonding force between the two, and improving the stability of the bonding between the two. The particle size of the diamond seed particles in the diamond powder layer is 100-1000 nm; preferably 400-800 nm.
[0009] The main function of the diamond coarse crystal bottom layer is to further reduce the large internal stress in the diamond coating caused by the large difference in thermal expansion coefficient between the cemented carbide and the diamond coating, and to improve the bonding force between the cemented carbide substrate and the diamond coating. The thickness of the diamond coarse crystal bottom layer is preferably 5-7 microns. The diamond coarse crystal grain size in the diamond coarse crystal bottom layer is greater than 1 μm, preferably 1-3 μm.
[0010] The main function of the diamond ultrafine crystal surface layer is to improve the smoothness of the diamond coating surface and reduce the surface roughness, which is beneficial to reduce the friction between the diamond coating thread core head and the copper tube during the drawing process of the threaded copper tube drawing die, thereby improving work efficiency. The surface roughness of the diamond ultrafine crystal surface layer is less than 100 nm; preferably, its surface roughness is 50-80 nm. The friction coefficient of the diamond ultrafine crystal surface layer is preferably 0.08-0.12, and the thickness is preferably 1-2 microns. The diamond ultrafine crystal grain size in the diamond ultrafine crystal surface layer is ≤100nm.
[0011] In order to avoid the influence of the large thickness of coarse crystal growth on the overall surface roughness of the coating, and to avoid the formation of large clusters due to the long growth time of ultra-nano crystals which in turn affects the surface smoothness, the diamond coating also includes a transition layer stacked between the diamond coarse crystal base layer and the diamond ultra-fine crystal surface layer, and the grain size in the transition layer is smaller than the grain size of the diamond coarse crystal and larger than the grain size of the diamond ultra-fine crystal.
[0012] The material of the cemented carbide substrate is mainly cemented carbide with tungsten carbide and cobalt as main components.
[0013] The present invention also provides a method for preparing the diamond-coated threaded core head, comprising the following steps: Chemical pretreatment: removing metal carbides on the surface of the cemented carbide substrate by chemical methods to form a rough surface; Forming a seed crystal layer: using a diamond powder suspension to ultrasonically treat the cemented carbide substrate that has been chemically pretreated, so as to form a seed crystal layer on the rough surface; Depositing diamond coating: using carbon-containing gas and hydrogen as raw materials, using chemical vapor deposition (CVD) method to deposit the diamond powder layer, diamond coarse crystal bottom layer and diamond ultrafine crystal surface layer on the rough surface; Polishing treatment: polishing treatment is performed on the diamond ultrafine crystal surface layer.
[0014] The purpose of the chemical pretreatment is mainly to roughen the surface of the cemented carbide substrate to form a rough surface. Specifically, the step of the chemical pretreatment includes treating the cemented carbide substrate with a Murakami reagent to remove metal carbides on the surface of the cemented carbide substrate and its surroundings, such as WC particles, to obtain a rough surface. The chemical pretreatment time is preferably 40-80 min.
[0015] Since Co can transform the diamond phase C in the diamond coating into the graphite phase C, in order to ensure the performance of the diamond coating, when the cemented carbide substrate contains Co, the step of chemical pretreatment also includes acid treatment of the cemented carbide substrate formed with a rough surface to remove the binder Co therein. The solvent used in the acid treatment is an acidic solution, mainly composed of concentrated hydrogen peroxide solution and concentrated acid. Preferably, the acidic solution is formed by uniformly mixing concentrated hydrogen peroxide solution and concentrated hydrochloric acid in a mass ratio of 2.5: 7.5-3.5: 6.5. Depending on the cobalt content of the cemented carbide, the acid treatment time is 7-60s.
[0016] The step of depositing the diamond coating is mainly prepared by pyrolyzing the carbon-containing gas by hot wire chemical vapor deposition (HFCVD). In the process of depositing the entire diamond coating, a 0.3-0.55 mm tantalum wire is used as the hot wire, the hot wire power is 5-10 kW, and the hydrogen flow rate is 1000-2000 sccm. In the process of depositing the diamond coarse crystal base layer, the seed crystal layer formed on the rough surface of the cemented carbide substrate is converted into a diamond micropowder layer, and the diamond coarse crystal base layer is deposited on the diamond micropowder layer to form the diamond coarse crystal base layer; the entire deposition process parameters of the diamond coarse crystal base layer include: gas pressure of 15-20 torr, methane flow of 10-30 sccm, thickness of 5-7 microns, and deposition time of 8-16 h. The deposition process parameters of the diamond ultrafine crystal surface layer include: gas pressure of 4-6 torr, methane flow of 40-100 sccm, thickness of 1-2 microns, and deposition time of 1-5 h.
[0017] The step of depositing the diamond coating also includes depositing a transition layer between the coarse-grained diamond base layer and the ultrafine-grained diamond surface layer by HFCVD method. The transition layer is a diamond transition layer, and its deposition process parameters include: gas pressure of 5-10 torr, methane flow rate of 20-70 sccm, thickness of 1-2 microns, and deposition time of 4-8 hours.
[0018] The main purpose of the polishing treatment is to further reduce the friction coefficient of the diamond coating in the diamond-coated threaded core head. Specifically, 3000-20000# diamond abrasive particles are mixed with an aqueous solution and attached to a gel ball with a particle size of 0.5-2mm, and the diamond ultrafine crystal surface layer of the threaded core head is treated for 1-5 minutes through an air nozzle at a spray angle of 30-60° and a pressure of 0.5-0.8mPa. Among them, the polishing time is preferably 1-3 minutes. Among them, a jet polisher can be used to achieve the polishing treatment of the diamond ultrafine crystal surface layer. The jet polisher is preferably an aerolap polisher.
[0019] The present invention also provides an application of the diamond-coated threaded core head in the preparation of an internally threaded copper tube, thereby improving the service life and working efficiency of the threaded core head as a drawing die for the internally threaded copper tube. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic structural diagram of a diamond-coated threaded core head provided in Example 1 of the present invention; Figure 2 An optical microscope image of the surface of the diamond coarse crystal base layer in the threaded core head provided in Example 1 of the present invention; Figure 3 An optical microscope image of the diamond coating surface of the diamond coating threaded core head provided in Example 1 of the present invention; Figure 4 A schematic diagram of the results of a diamond-coated threaded core head provided in Example 2 of the present invention; Figure 5 An optical microscope image of the surface of the diamond coating in the threaded core head provided in Example 2 of the present invention; Figure 6 An optical microscope image of the diamond coating surface of the threaded core head provided for Comparative Example 1; Figure 7 An optical microscope image of the diamond coating surface of the threaded core head provided for Comparative Example 2; Figure 8 A comparison diagram of the use status of the threaded core head provided for Example 2 (right, supercrystalline layer polished) and Comparative Example 3 (left, supercrystalline layer not polished) as a drawing die for an internally threaded copper tube; Among them, in the above figure: 1 tungsten-cobalt cemented carbide substrate, 2 diamond powder layer, 3 diamond coarse crystal base layer, 4 diamond ultrafine crystal surface layer, 5 transition layer. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0022] The terms used in the present invention are all commonly used terms in the relevant field. The raw materials, equipment, preparation processes, testing methods, etc. used are all prior arts in the relevant field unless otherwise specified.
[0023] Among them, the main reagent solutions used in each embodiment are as follows: Murakami reagent: K3[Fe(CN)]6: KOH: H2O = 1:1:10 (mass ratio); Acidic solution: concentrated H2O2 solution and concentrated hydrochloric acid (HCl) are uniformly mixed in a mass ratio of 3:7, and the mass concentration of the concentrated H2O2 solution is 30%, and the mass concentration of the concentrated hydrochloric acid is 36.5%; Diamond micro powder suspension: mainly composed of 100 nm diamond micro powder and anhydrous ethanol.
[0024] Aero lap polisher originated from Yamashita Co., Ltd.
[0025] Example 1 See also Figure 1 An embodiment of the present invention provides a diamond-coated threaded core head, comprising a cemented carbide substrate 1 and a diamond coating formed on the surface 1 of the cemented carbide substrate, wherein the diamond coating comprises a diamond micropowder layer 2, a diamond coarse-grained bottom layer 3, and a diamond ultrafine-grained surface layer 4 formed on the surface of the tungsten-cobalt cemented carbide substrate 1 in sequence from bottom to top.
[0026] This embodiment also provides a method for preparing the diamond-coated threaded core head, which mainly includes the steps of chemical pretreatment, forming a seed crystal layer, depositing a diamond coating, and polishing. Specifically, the method includes the following steps: The chemical pretreatment comprises the following steps: Roughening treatment: The surface of the tungsten-cobalt cemented carbide substrate was treated with Murakami reagent for 50 min to remove a large number of WC particles on the substrate surface and nearby to obtain a rough surface; Acid treatment: The cemented carbide substrate with a rough surface is treated with an acid solution for 40 seconds to remove the binder Co therein, thereby obtaining an acid-treated substrate.
[0027] The step of forming the seed crystal layer comprises: firstly ultrasonically treating the acid-treated substrate in a diamond micropowder suspension for 20 minutes, retaining a certain number of diamond nanoparticles on the rough surface as nucleation sites in the subsequent coating formation process, as diamond seed crystals; and then ultrasonically treating the substrate surface with the diamond seed crystals in an acetone solution for 20 minutes to clean the substrate surface, thereby obtaining a clean substrate.
[0028] The step of depositing the diamond coating is mainly completed by using HFCVD equipment. During the entire diamond coating process, the hot wire power of the equipment is 6 kW, and a 0.55 mm tantalum wire is used as the hot wire. The hydrogen flow rate is 1400 sccm, and the specific coating process is divided into two stages: The diamond coarse crystal layer was formed, the gas pressure was 16 torr, the methane flow rate was 15 sccm, and the coating time of this stage was 14 hours, so that the seeds in the seed layer on the roughened surface grew to form a diamond coarse crystal layer 3 with a thickness of about 6 microns, and the grain size was 1-3 μm, such as Figure 2 As shown; wherein the seed crystal layer is converted into a diamond powder layer 2, and the grain size thereof is 400-800 nm; To form a diamond ultrafine crystal surface layer, the gas pressure was reduced to 4 torr, the methane flow rate was increased to 70 sccm, the coating time was 4 h, and a diamond ultrafine crystal surface layer 4 with a thickness of about 2 microns was formed, and its grain size was 40-60 nm.
[0029] Polishing treatment: Polishing the ultrafine diamond surface layer 4. Mix 10000# diamond abrasive grains with aqueous solution and attach them to a small gel ball with a particle size of 1.5 mm. Polish the ultrafine diamond surface layer for 2 min at a spray angle of 45° and a pressure of 0.65 mPa through an air nozzle to obtain an ultrafine crystal surface layer with a roughness of about 85 nm after polishing. Figure 3 shown.
[0030] Example 2 See also Figure 4 The present embodiment provides a diamond coated thread core head and a preparation method thereof, which is mainly different from the diamond coated thread core head and a preparation method thereof provided in Example 1 in that: the diamond coated thread core head provided in the present embodiment has a transition layer 5 disposed between the diamond coarse crystal base layer 3 and the diamond ultrafine crystal surface layer 4; the preparation method of the transition layer 5 comprises: after forming the diamond coarse crystal base layer 3, reducing the gas pressure to 10 torr, increasing the methane flow rate to 28 sccm, and coating for 8 h; thereby forming a transition layer 5 on the diamond coarse crystal base layer 3, and the grain size thereof is 100-1000 nm; after forming the transition layer 5, depositing a transition layer 5 on the transition layer 5 as shown in FIG. Figure 5 (left) shows the diamond ultrafine crystal surface layer. The diamond ultrafine crystal surface layer is polished to obtain the following Figure 5 (Right) The diamond ultrafine-grained surface layer 4 shown has a roughness of about 60 nm.
[0031] Example 3 This embodiment provides a diamond-coated threaded core head and a preparation method thereof, which has a structure substantially the same as that provided in Embodiment 2, and the preparation method thereof comprises the following steps: The chemical pretreatment comprises the following steps: Roughening treatment: The surface of the tungsten-cobalt cemented carbide substrate was treated with Murakami reagent for 40 min to remove a large number of WC particles on the substrate surface and nearby to obtain a rough surface; Acid treatment: The cemented carbide substrate with a rough surface is treated with an acid solution for 30 seconds to remove the binder Co therein, thereby obtaining an acid-treated substrate.
[0032] The step of forming the seed crystal layer comprises: firstly ultrasonically treating the acid-treated substrate in a diamond micropowder suspension for 15 minutes, leaving a certain number of diamond nanoparticles on the rough surface as nucleation sites in the subsequent coating formation process, as diamond seed crystals; and then ultrasonically treating the substrate surface with the diamond seed crystals in an acetone solution for 10 minutes to clean the substrate surface, thereby obtaining a clean substrate.
[0033] The step of depositing the diamond coating is mainly completed by using HFCVD equipment. During the entire diamond coating process, the hot wire power of the equipment is 6 kW, and a 0.40 mm tantalum wire is used as the hot wire. The hydrogen flow rate is 2000 sccm, and the specific coating process is divided into two stages: A diamond coarse crystal layer is formed, the gas pressure is 20 torr, and the methane flow rate is 25 sccm. The coating time of this stage is 12 hours, so that the seeds in the seed layer on the roughened surface grow to form a diamond coarse crystal layer with a thickness of about 8 microns and a grain size of 1-3 μm; and the seed layer is converted into a diamond micro powder layer, in which the grain size is 100-500 nm; To form a transition layer, the gas pressure is first reduced to 10 torr, the methane flow rate is increased to 35 sccm, and the coating time is 6 hours, thereby forming a transition layer on the diamond coarse crystal base layer, and the grain size of the transition layer is 100-1000 nm; To form a diamond ultrafine-crystalline surface layer, the gas pressure was reduced to 5 torr, the methane flow rate was increased to 90 sccm, and the coating time was 3 hours, forming a diamond ultrafine-crystalline surface layer with a thickness of about 2 microns and a grain size of 30-100 nm.
[0034] Polishing treatment: Polishing the ultrafine-grained diamond surface layer: 10000# diamond abrasive grains were mixed with an aqueous solution and attached to a small gel ball with a particle size of 1.5 mm. The ultrafine-grained diamond surface layer was polished for 2 min at a spray angle of 45° and a pressure of 0.65 mPa through an air nozzle to obtain a diamond ultrafine-grained surface layer with a roughness of about 68 nm after polishing.
[0035] Performance Verification The friction coefficient and processing effect of the diamond coated threaded core heads provided in Examples 1-3 and Comparative Examples 1-3 were tested below, and the results are shown in Table 1. The friction coefficient is calculated in combination with the friction and wear test, and the processing effect is mainly evaluated based on the quality of the internal threaded copper tube processed by each diamond coated threaded core head.
[0036] Comparative Example 1 provides a diamond coated threaded core head, which is mainly different from the spiral core head provided in Example 1 in that: in Comparative Example 1, a diamond coarse crystal base layer is used as the surface layer, that is, it does not contain a diamond ultrafine crystal surface layer, and the other structures and preparation methods are the same as those in Example 1. The optical microscope images of the coarse crystal layer before and after polishing are as follows: Figure 6 shown.
[0037] Comparative Example 2 provides a diamond-coated threaded core head, which is mainly different from the spiral core head provided in Example 2 in that the thickness of the diamond ultrafine crystal surface layer in Comparative Example 2 is 3.5 microns. Figure 7 As shown, the coating formation time in the preparation process of the ultrafine-grained diamond surface layer is extended to 8 h, and the rest is the same as in Example 1.
[0038] Comparative Example 3 provides a diamond-coated threaded core head, which is mainly different from the spiral core head provided in Example 2 in that the diamond ultrafine crystal surface layer prepared in Comparative Example 3 is not polished, that is, the surface of the diamond coating is as follows: Figure 5 The use status of the internal thread copper tube drawing die made by the core head of this comparative example and embodiment 2 is as follows Figure 8 shown.
[0039] Table 1 Performance test results of diamond coated thread core head
[0040] Combining Table 1, it can be seen that, by comparing Example 1 with Comparative Example 1, the outermost layer of Example 1 is a diamond ultrafine crystal layer, and the outermost layer of Comparative Example 1 is a diamond coarse crystal layer. Since the grains in the diamond coarse crystal layer are relatively large, there are fewer grain boundaries, the content of SP3 bonds is high, and the coating is relatively hard, it is difficult to make the surface smooth after polishing, and the roughness is relatively high. Figure 6 As shown; however, the diamond ultrafine crystal layer has finer grains and more grain boundaries. The higher the content of SP2 bonds, the more polishing can be performed on the diamond ultrafine crystal layer, such as Figure 5 Therefore, the friction coefficient of the diamond coating in Example 1 is relatively small, the friction force during the core head pulling process is small, the processing volume is relatively large, the service life is relatively long, and the working efficiency is relatively high.
[0041] Combination Figure 2 and Figure 7 By comparing Example 1 with Comparative Example 2, it can be seen that the ultra-nanocrystalline growth time is too long, the coating is thick, and large clusters are likely to appear, which in turn affects the surface smoothness. Figure 7 The red frame shows the clustering phenomenon that occurs when the ultrafine crystal coating is thicker. As a result, during the drawing process of the internal threaded copper tube, the clustered part is significantly higher than other positions, which can easily scratch the internal threaded copper tube. At the same time, it can easily cause the surface quality of the produced internal threaded copper tube to be substandard and the processing performance to be poor.
[0042] By comparing Example 2 and Comparative Example 3, it can be seen that the inner surface of the internal threaded copper tube has higher quality requirements after drawing. The surface roughness caused by the chemical pretreatment process during the formation of the diamond coating will be replicated on the coating surface during the coating process. Although the ultra-nanocrystalline coating has a low friction coefficient, the overall coating hardness is high. When drawing the internal threaded copper tube, the copper tube can be scratched in a short processing time, resulting in copper sticking. Figure 8 (left) As shown, the quality of the internal threaded copper tube does not meet the standard. The gel ball polishing treatment provided in Example 2 can effectively remove the raised part of the ultra-nanocrystalline coating, making the core head surface smooth. After a single diamond-coated threaded core head processes 50 tons of internal threaded copper tubes, its surface is as follows Figure 8 (Right) As shown, copper sticking does not occur, and the qualified product requirements of internal thread copper pipes are met until the product is processed to 61 tons.
[0043] It can be seen from the combination of Examples 1 and 2 that the provision of a transition layer in the diamond coating is beneficial to reducing the surface friction coefficient of the diamond coated threaded core head and increasing the processing volume of the diamond coated threaded core head.
[0044] Therefore, the diamond coated thread core head provided in the embodiment of the present invention is mainly coated with diamond on the surface of the cemented carbide thread core head by the HFCVD method. The diamond coating is a coating with extremely high wear resistance, good anti-adhesion and strong thermal conductivity. The coating thickness of the CVD method can reach more than 10 microns. It has the characteristics of high strength, good toughness, good wear resistance and low friction coefficient. It can effectively improve the service life of the thread core head, so that a single diamond coated thread core head can process 50 to 65 tons of internal threaded copper pipes; the diamond coated thread core head provided in the embodiment of the present invention has a low friction coefficient, which is also conducive to improving processing efficiency and reducing costs.
[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A diamond coated thread core head, characterized in that: The invention comprises a cemented carbide substrate and a diamond coating formed on the surface of the cemented carbide substrate, wherein the diamond coating comprises a diamond micro-powder layer, a diamond coarse crystal bottom layer and a diamond ultra-fine crystal surface layer formed on the surface of the cemented carbide substrate, and the diamond coarse crystal bottom layer is stacked between the diamond micro-powder layer and the diamond ultra-fine crystal surface layer, wherein the surface roughness of the diamond ultra-fine crystal surface layer is less than 100 nm; Preferably, the surface roughness of the ultrafine-grained diamond surface layer is 50-80 nm; Preferably, the diamond grain size in the diamond powder layer is 100-1000 nm; Preferably, the cemented carbide substrate is a cemented carbide mainly composed of tungsten carbide and cobalt.
2. The thread core head according to claim 1, characterized in that: The thickness of the ultrafine diamond surface layer is 1-2 microns, and the ultrafine diamond grain size is ≤100 nm; Preferably, the friction coefficient of the ultrafine-grained diamond surface layer is 0.08-0.
12.
3. The thread core head according to claim 1, characterized in that: The thickness of the diamond coarse crystal bottom layer is 5-7 microns, and the grain size of the diamond coarse crystal therein is greater than 1 μm.
4. The thread core head according to claim 1, 2 or 3, characterized in that: The diamond coating further comprises a transition layer stacked between the diamond coarse crystal bottom layer and the diamond ultrafine crystal surface layer, wherein the grain size of the transition layer is smaller than the grain size of the diamond coarse crystal and larger than the grain size of the diamond ultrafine crystal.
5. A method for preparing a diamond-coated threaded core head according to any one of claims 1 to 4, comprising the following steps: Chemical pretreatment: removing metal carbides on the surface of the cemented carbide substrate by chemical methods to form a rough surface; Forming a seed crystal layer: using a diamond powder suspension to ultrasonically treat the cemented carbide substrate that has been chemically pretreated, so as to form a seed crystal layer on the rough surface; Depositing diamond coating: using carbon-containing gas and hydrogen as raw materials, using chemical vapor deposition method to deposit the diamond powder layer, diamond coarse crystal bottom layer and diamond ultrafine crystal surface layer on the rough surface respectively; Polishing treatment: polishing treatment is performed on the diamond ultrafine crystal surface layer.
6. The preparation method according to claim 5, characterized in that The step of depositing the diamond coating is mainly prepared by pyrolyzing the carbon-containing gas by hot wire chemical vapor deposition, and in the process of depositing the entire diamond coating, a 0.3-0.55 mm tantalum wire is used as the hot wire, the hot wire power is 5-10 kW, and the hydrogen flow rate is 1000-2000 sccm.
7. The preparation method according to claim 6, characterized in that The step of depositing the diamond coating includes converting the seed crystal layer into a diamond powder layer during the process of depositing the diamond coarse crystal coating layer; and the deposition process parameters of the diamond coarse crystal coating layer include: gas pressure of 15-20 torr, methane flow rate of 10-30 sccm, and deposition time of 8-16 h.
8. The preparation method according to claim 7, characterized in that The deposition process parameters of the diamond ultrafine crystal surface layer include: gas pressure of 4-6 torr, methane flow rate of 40-100 sccm, and deposition time of 1-5 h.
9. The preparation method according to claim 8, characterized in that: The step of depositing the diamond coating also includes depositing a transition layer between the diamond coarse crystal bottom layer and the diamond ultrafine crystal surface layer; Preferably, the deposition process parameters of the transition layer include: gas pressure of 5-10 torr, methane flow rate of 20-70 sccm, and deposition time of 4-8 h.
10. The preparation method according to any one of claims 5 to 9, characterized in that: The polishing step includes using 3000-20000# diamond abrasives mixed with an aqueous solution to attach to a gel ball with a particle size of 0.5-2 mm, and treating the diamond ultrafine crystal surface layer for 1-5 minutes through an air nozzle at a spray angle of 30-60° and a pressure of 0.5-0.8 mPa.
11. The preparation method according to claim 5, characterized in that: The chemical pretreatment step includes treating the cemented carbide substrate with a Murakami reagent to remove metal carbides on the surface of the cemented carbide substrate and its surroundings to obtain a rough surface; Preferably, the chemical pretreatment time is 40-80 min.
12. The preparation method according to claim 6, characterized in that: The chemical pretreatment step further includes acid treatment of the cemented carbide substrate having a rough surface to remove the binder Co therein; Preferably, the acid treatment time is 7-60 s; Preferably, the acid treatment is carried out using an acidic solution, and the acidic solution mainly consists of a concentrated hydrogen peroxide solution and a concentrated acid; Preferably, the acidic solution is formed by uniformly mixing concentrated hydrogen peroxide solution and concentrated hydrochloric acid in a mass ratio of 2.5:7.5-3.5:6.
5.
13. Use of the diamond-coated threaded core head according to any one of claims 1 to 4 in the preparation of an internally threaded copper tube.
Citation Information
Patent Citations
Method for prolonging service life of internal thread core head
CN112877618A